The influence of soil moisture on threshold runoff generation processes in an alpine headwater catchment - D. Penna (Hydrology and Earth System Sciences, 2011)
This study investigates the role of soil moisture on the threshold runoff response in a small headwater catchment in the Italian Alps that is characterised by steep hillslopes and a distinct riparian zone. This study focuses on: (i) the threshold soil moisture-runoff relationship and the influence of catchment topography on this relation; (ii) the temporal dynamics of soil moisture, streamflow and groundwater that characterize the catchment's response to rainfall during dry and wet periods; and (iii) the combined effect of antecedent wetness conditions and rainfall amount on hillslope and riparian runoff. Our results highlight the strong control exerted by soil moisture on runoff in this catchment: a sharp threshold exists in the relationship between soil water content and runoff coefficient, streamflow, and hillslope-averaged depth to water table. Low runoff ratios were likely related to the response of the riparian zone, which was almost always close to saturation. High runoff ratios occurred during wet antecedent conditions, when the soil moisture threshold was exceeded. In these cases, subsurface flow was activated on hillslopes, which became a major contributor to runoff. Antecedent wetness conditions also controlled the catchment's response time: during dry periods, streamflow reacted and peaked prior to hillslope soil moisture whereas during wet conditions the opposite occurred. This difference resulted in a hysteretic behaviour in the soil moisture-streamflow relationship. Finally, the influence of antecedent moisture conditions on runoff was also evident in the relation between cumulative rainfall and total stormflow. Small storms during dry conditions produced low stormflow amounts, likely mainly from overland flow from the near saturated riparian zone. Conversely, for rainfall events during wet conditions, higher stormflow values were observed and hillslopes must have contributed to streamflow.